Optimization of Website Development to Increase Export Sales of Stone Resin Products: A Case Study of Pt. Als Pra Capital - Alma Sukmawati Harun (Riviera Publishing, 2024)
In the era of growing international trade, the use of digital technology has become very important for companies to increase their competitiveness. This research aims to optimize the use of PT Als Pra Capital's website as a digital marketing tool to increase export sales of Damar Batu products. The methods used include the Design Thinking approach, SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, and STP (Segmentation, Targeting, Positioning) to design a website prototype that supports e-commerce functionality and improves company branding. The results of the website prototype development show that the implementation of an effective digital marketing strategy can increase the visibility and accessibility of Damar Batu products in the international market. The discussion highlights that by optimizing the website and implementing appropriate digital marketing strategies, PT Als Pra Capital is expected to expand their export market share and strengthen their position in the global market. This research contributes to the development of digital marketing strategies in the export sector.